Intermediate Filaments at the Junction of Mechanotransduction, Migration, and Development - Sanghvi-Shah, Rucha; Weber, Gregory F. (Frontiers in Cell and Developmental Biology, 2017)
Mechanically induced signal transduction has an essential role in development. Cells actively transduce and respond to mechanical signals and their internal architecture must manage the associated forces while also being dynamically responsive. With unique assembly-disassembly dynamics and physical properties, cytoplasmic intermediate filaments play an important role in regulating cell shape and mechanical integrity. While this function has been recognized and appreciated for more than 30 years, continually emerging data also demonstrate important roles of intermediate filaments in cell signal transduction. In this review, with a particular focus on keratins and vimentin, the relationship between the physical state of intermediate filaments and their role in mechanotransduction signaling is illustrated through a survey of current literature. Association with adhesion receptors such as cadherins and integrins provides a critical interface through which intermediate filaments are exposed to forces from a cell’s environment. As a consequence, these cytoskeletal networks are posttranslationally modified, remodeled and reorganized with direct impacts on local signal transduction events and cell migratory behaviors important to development. We propose that intermediate filaments provide an opportune platform for cells to both cope with mechanical forces and modulate signal transduction.